Strengthening Community-Based Sustainable Ecotourism through Hospitality and Coffee Service Training in Bogor Waqf Forest - Khalifah Muhamad Ali; Mu'minah Mustaqimah; Miftahul Jannah; Rodhiyatan Mardhiyyah; Rahman Maulana; Edih Edih; Sahrudin Sahrudin; Fadhil Jamaluddin; Muhammad Arsyil Abdillah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Waqf-based forests represent a sustainable forest management initiative that is expanding in Indonesia, integrating Islamic principles of waqf with forest management practices. Preliminary research indicated that communities surrounding Bogor Waqf Forest, one example of waqf-based forest implementation, have low income levels and expressed expectations for additional income-generating activities. This training aimed to prepare local communities around Bogor Waqf Forest to enhance sustainable ecotourism services, including hospitality and coffee service. This service-oriented capacity building was designed as a productive waqf strategy to strengthen community roles in developing sustainable ecotourism. The study applied a community-based training approach with post-test evaluation. The training comprised two sessions, namely (1) a hospitality and service excellence session and (2) a coffee training session. Based on post-test results, participants demonstrated improved knowledge and practical skills in hospitality, including receiving and serving guests, as well as in coffee preparation, including brewing and preparing several variations of coffee beverages for visitors. Overall, the training supports the productivity of waqf-based forests by equipping communities with competencies needed for community-based sustainable ecotourism.